Potential Feature of Combined AB5-Type Metal Hydride Tank and PEMFC as a Safer System for Hydrogen Fueling in Bangladesh - Salam, Md Abdus; Islam, Thauhidul; Ahmed, Kawsar; Sahab uddin, Md; Habib, Shehan; Abdullah, Bawadi (Frontiers in Energy Research, 2021)
Metal hydrides are very much reported as a potential safe option for high-density hydrogen storage materials. A combined system of proton-exchange membrane hydrogen fuel cell (PEMFC) and metal hydride (MH) tanks is designed to investigate their characteristics and performances as hydrogen storage and stable power supply system. An AB5-type (LaCe)Ni5 material containing three MH tanks is selected for investigation. Endothermic dehydrogenation of metal hydride controls the hydrogen evolution rates during a discharging period, which reduces the risk of accidents. The MH tank charged at a 20°C water bath sustains and supplies hydrogen for a longer time of 240 min. The performances of the MH tank at a water bath of 20°C and 10-bar conditions correspond to the optimum condition of hydrogen storage at the MH tank of Pragma Industries. The performances of the combined system were investigated in different working conditions. The system sustains and supplies hydrogen to PEMFC for 240, 160, 130, and 110 min for the working loads of 250, 500, 1,000, and 2,000 W, accordingly. It is concluded that hydrogen consumption frequency increases for higher load demand.